Adsorption : the new frontier in extracorporeal blood purification - Bellomo, Rinaldo 1956-; Ronco, Claudio 1951- (Contributions to nephrology / series editor Claudio Ronco, 2023)
2023 is the time to collect available knowledge and basic concepts around extracorporeal blood purification in a book that may become the basis for expansion of awareness in the scientific community and a stimulus for new studies and new discoveries by scientists and investigators. We need to answer the question for hemoadsorption that we answered in the last four decades for hemodialysis and CRRT. The pathway towards the new frontier of hemoadsorption starts from this book.